Special Issue on Designing Hydrogels for Controlled Drug Delivery: Guest Editors' Introduction - Sonia Trombino; Roberta Cassano (MDPI AG, 2020)
Hydrogels have received growing attention in recent years as materials for drug delivery systems (DDS), because they are biocompatible and nontoxic [...]